Towards sound athletic talent development. The Danish dual career model - Stilling Olesen, J.; Stausgaard Skrubbeltrang, L.; Karen, D.; J. C. Nielsen (Routledge, 2026)
Towards Sound Athletic Talent Development addresses a fundamental question in its comprehensive analysis of Denmark`s unique approach to early athletic talent development: How can we develop world-class athletes without compromising their well-being, education, or identity? Central to Denmark`s approach, the book shows, is a commitment to "sound" development, a carefully constructed path that balances the pursuit of elite performance with the broader needs of growing individuals, and a path in which the authors explore in depth in this book.